Comment Reduced Parenthetical Clauses and the syntax-discourse interface - Matos, Gabriela (Revista Letras, 2019)
Reduced parenthetical clauses (RPCs) in European Portuguese have not been studied until recently. Focusing on comment RPCs, a preliminary classification of the most common verbal predicates in this context is set up for this language, and their pragmatic values established. The distribution of comment RPCs, especially their floating status and the blocking of c-command from the host sentences, indicates that they are syntactically related to their hosts by a paratactic link, as parenthetical modifiers. As for the internal structure of the comment clause, island effects reveal that, in European Portuguese, the argument gap of the verb results from movement of a null category to an A-bar position of the parenthetical clause. Also, adverb placement shows that the verb and the subject occupy high discursive projections in the left periphery of the RPC, suggesting that the post-verbal subject is focalized in specifier of FocP. The contrasts between comment RPCs with null and overt subjects shows that in European Portuguese the mitigative pragmatic value of the RPC is not exclusively drawn from the epistemic, evidential or evaluative predicates, but also relies on the post verbal use of the subject.